Extensive resection improves overall and disease-specific survival in localized anorectal melanoma: A SEER-based study - Liu, Chang; Tang, Cuiping; Zhang, Jianbo; Zhu, Peng (Frontiers in Surgery, 2022)
Background: Anorectal melanoma is a rare tumor with a dismal prognosis. The only promising treatment for anorectal melanoma is surgery, either extensive resection (ER) or local excision (LE). However, the optimal extent of resection is still controversial. The purpose of this study was to investigate whether the survival outcomes of anorectal melanoma at different stages are influenced by the surgical approaches (LE or ER) using the National Institute of Health's Surveillance, Epidemiology, and End Results Program (SEER) database. Methods: The Surveillance, Epidemiology and End Results (SEER) database was queried to identify patients treated for anorectal melanoma (2000-2018). Overall survival (OS) and disease-specific survival (DSS) outcomes were compared for the two surgical approaches (ER or LE) stratified by stage (localized, regional and distant). Results: A total of 736 patients were included in the study. Details of previous surgical procedures were available for 548 of the study patients: 360 (65.7%) underwent LE, and 188 (34.3%) underwent ER. In localized cases,199 underwent LE, and 48 underwent ER. The OS (median 45 vs 29 months, 5-year rate 41.7% vs 23.4%) and DSS (median 66 vs 34 months, 5-year rate 51% vs 30.7%) of patients undergoing ER were significantly better (p=0.009 and 0.041, respectively) than those who received LE. Multivariate analysis showed that the type of surgery was an independent prognostic factor for both OS and DSS. Among the regional cases, 89 cases had LE, and 96 cases had ER. Patients with regional disease who underwent ER had no significant differences in OS (23 vs 21 months; p=0.866) or DSS (24 vs 24 months; p=0. 907) compared to patients who underwent LE. In distant cases, 72 cases had LE, and 44 cases had ER. Patients with metastatic disease who had ER also had similar OS (median 11 vs 8 months; P=0.36) and DSS (median 11 vs 8 months; P=0.593) to those who underwent LE. Conclusion: Extensive resection can improve the long-term prognosis of localized anorectal melanoma compared to local excision, but the prognosis of the two surgical techniques is comparable in both regional patients and distant patients.